A Porphyromonas gingivalis Tyrosine Phosphatase is a Multifunctional Regulator of Virulence Attributes - Maeda, Kazuhiko (2008)
Low Molecular Weight Tyrosine Phosphatases (LMWTP) are widespread in prokaryotes; however, understanding of the signaling cascades controlled by these enzymes is still emerging. P. gingivalis, an opportunistic oral pathogen, expresses a LMWTP, Ltp1, that is differentially regulated in biofilm communities. Here we characterize the enzymatic activity of Ltp1 and, through the use of mutants that lack Ltp1 or expresses catalytically defective Ltp1, show that tyrosine phosphatase activity constrains both monospecies biofilm development and community development with the antecedent oral biofilm constituent S. gordonii. Exopolysaccharide production is downregulated by Ltp1 through transcriptional regulation of multiple genes involved in biosynthesis and transport. Furthermore, Ltp1 regulates transcriptional activity of luxS and thus impacts AI-2 dependent signaling in biofilm communities. In the absence of Ltp1 transcription across the hmu hemin uptake locus is reduced, and consequently uptake of hemin is impaired in the Ltp1 mutant. The gingipain proteinases Kgp and RgpA/B remain phosphorylated in the Ltp1 mutant. Phosphorylated Rgps are poorly secreted, whereas cell surface activity of phosphorylated Kgp is enhanced. By controlling the activity of several virulence-associated properties, Ltp1 may restrain the pathogenic potential of P. gingivalis and maintain a commensal interaction with the host.